Competitive Power of Gondorukem Indonesia in International Market - Munim, Farhah Nikmatul; Nurfadillah, Suryani; Imam Santoso, Siswanto (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 1 (2024): Vol 18 No 1 (2024)DO - 10.24843/SOCA.2024.v18.i01.p01, 2024)
Indonesia is the first number exporting country of gondorukem in 2022 in the world. However, the government and community have not paid much attention to the development of gondorukem thereby affecting the optimum production. This research is intended to analyzing the competitive power and the determining factors of competitive power for gondorukem Indonesia in the framework of Porter’s Diamond Model . Data analysis in this research was made using the ISP analysis media and approach of Porter’s Diamond Model . Based on average score of ISP gondorukem Indonesia of 2013-2022, The position of maturation has most firm competitive power. Based on the analysis with Porter’s Diamond Model , we know that the competitive power of gondorukem Indonesia is affected by the condition factor, demand condition, supporting industry, and competition; structure; and strategy. Condition factor is indicated by the extensive pine land, many and cheap workers, sufficient capital, growth in knowledge, and sufficient infrastructure. Demand condition is indicated by the qualified domestic market demand. Supporting industry is indicated by the lot demand of gondorukem in the paint, ink, and batik industries. Competition, structure, and strategy are indicated by the control of production materials and market by BUMN Perum Perhutani, so it eases the development of gondorukem qualitatively and quantitatively. Information found related to the competitive superiority can be served as the reference of developing the domestic gondorukem.